2008
DOI: 10.1111/j.1475-6811.2007.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment, sexual satisfaction, and relationship satisfaction: A study of married couples

Abstract: The goal of this research was to extend prior work on adult attachment and sexuality, which has tended to focus on samples of adolescents and undergraduate students. A Canadian sample of 116 married couples aged 21–75 years completed self‐report measures of adult attachment, marital, and sexual satisfaction. Results revealed that participants with higher levels of anxiety and avoidance reported lower levels of sexual satisfaction at the individual level. Individuals with more avoidant spouses also reported low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
262
5
27

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(321 citation statements)
references
References 33 publications
27
262
5
27
Order By: Relevance
“…These results are similar to the ones found in community sample studies (Birnbaum, 2007;Butzer & Campbell, 2008;Davis et al, 2006;Fricker & Moore, 2002) as well as in studies of clinically distressed couples (Brassard et al, 2012). Many reasons can explain why anxiously attached women with PVD are less satisfied with their sexual experiences.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These results are similar to the ones found in community sample studies (Birnbaum, 2007;Butzer & Campbell, 2008;Davis et al, 2006;Fricker & Moore, 2002) as well as in studies of clinically distressed couples (Brassard et al, 2012). Many reasons can explain why anxiously attached women with PVD are less satisfied with their sexual experiences.…”
Section: Discussionsupporting
confidence: 86%
“…Correlational studies already show that attachment anxiety is associated with poorer sexual experiences (Birnbaum, 2007;Brassard, Peloquin, Dupuy, Wright, & Shaver, 2012;Butzer & Campbell, 2008;Costa & Brody, 2011;Davis et al, 2006;Gentzler & Kerns, 2004) and greater sex-related worries (Birnbaum et al, 2006;Davis et al, 2006). Two studies using a dyadic approach have shown interesting partner effects indicating that an individual's attachment can predict their partner's sexual outcome (Brassard et al, 2012;Butzer & Campbell, 2008). More specifically, Brassard et al (2012) found that men's attachment anxiety was associated with higher sexual dissatisfaction in women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No casal 3, que descreveu mais expectativas em relação a retomar a conjugalidade e trouxe mais queixas nesse sentido, o aspecto sexual e de romantismo foi bastante enfocado. De fato, existem estudos que relacionam o apego com a sexualidade (BUTZER;CAMPBELL, 2008;HOLMES, 2007;BRASSARD;SHAVER;LUSSIER, 2007). Esses estudos ressaltam que o contato físico íntimo é importante na infância e na vida adulta: para a criança, no desenvolvimento do vínculo de apego inicial e para os parceiros românticos a busca da proximidade ocorre também através da atração sexual.…”
Section: Discussionunclassified
“…Furthermore, albeit numerous studies on influence of one's attachment patterns on relationship quality were conducted (e.g., Butzer & Campbell, 2008;Towler & Stuhlmacher, 2013), exists the dyadic perspective which reflects classic ideas of internal working models origin: the dimensions of avoidance and anxiety (basic parameters for two-dimensional model of individual differences of romantic attachment) in oneself and his/ her romantic partner are interrelated. The attachment insecurity indicators and its' perception in couples members are related with relationship satisfaction (Molero et al, 2016).…”
Section: Introductionmentioning
confidence: 99%